2001
DOI: 10.1088/0022-3727/34/12/321
|View full text |Cite
|
Sign up to set email alerts
|

Extended-field electromagnetic model for inductively coupled plasma

Abstract: An extended-field (EF), two dimensional (2D) model formulation is proposed for inductively coupled plasma. By extending the calculating domain of the electromagnetic (EM) field outside of the plasma discharge region, the boundary conditions of vector potential used by the standard (ST) 2D model are replaced by simpler far field boundary conditions. The extended model converges faster than the standard formulation and gives rise to consistent solutions throughout the computational domain. Vector potential equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 15 publications
7
92
0
1
Order By: Relevance
“…However, at the same time, this simple case does not consider a current density variation in axial or radial directions and only the axial component was considered. It is known that the distance of the boundary condition from the conducting zone can affect the accuracy of the results [12][13]. This point will be studied further in the geometry involving the electric arc.…”
Section: Iii/ Validation Of the Electromagnetic Modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, at the same time, this simple case does not consider a current density variation in axial or radial directions and only the axial component was considered. It is known that the distance of the boundary condition from the conducting zone can affect the accuracy of the results [12][13]. This point will be studied further in the geometry involving the electric arc.…”
Section: Iii/ Validation Of the Electromagnetic Modelsmentioning
confidence: 97%
“…This specific condition cannot be reached in all models (problems in constricted parts and necessity to assume a large calculation domain). This point has been studied by some authors in RF plasmas configurations where people propose to calculate the magnetic field in an extended domain [12] [13] or by B&S equations [12]. In AC/DC, in order to overcome this problem, the authors very often consider a null flux as boundary condition for vector potential components at the modelled geometry edges [9][10] or a value equal to zero if the boundary is far from the arc [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal plasmas are assumed to be under partial to complete local thermodynamic equilibrium (LTE) conditions. Under LTE, the plasma can be considered a conductive fluid mixture and therefore, be modeled using the magnetohydrodynamics (MHD) equations, [1]. This model shows how to use the equilibrium inductively coupled discharge interface to simulate the plasma generated in an inductively coupled plasma, [1]- [2].…”
Section: Introductionmentioning
confidence: 99%
“…Under LTE, the plasma can be considered a conductive fluid mixture and therefore, be modeled using the magnetohydrodynamics (MHD) equations, [1]. This model shows how to use the equilibrium inductively coupled discharge interface to simulate the plasma generated in an inductively coupled plasma, [1]- [2]. The main objective of this work is to investigate: the effect of Increasing number of turns in a coil and the effect of electrical current both on the plasma temperature distribution, and the electron density of the argon plasma II.…”
Section: Introductionmentioning
confidence: 99%
“…al. [19] proposed a novel 2D model to study the influence of coil angle on temperatures and flow field. The results indicated that the influence of coil angle on temperature and flow field does not have noticeable change.…”
Section: Introductionmentioning
confidence: 99%